Pemanfaatan Media Adobe Animate untuk Meningkatkan Pemahaman Konsep Perubahan Wujud Benda dan Sifatnya di Sekolah Dasar - Salsabila, Siti Naida Aulia; Lestari, Sri Ayu; Herman, Syafira Awalia; Heryadi, Yadi (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study aims to determine the effectiveness of the use of Adobe Animate media to optimize students' understanding of the concept of changing the shape of objects and their properties at the elementary school level in grade IV. The background of this research is based on the low level of students' understanding of concrete science concepts, such as changes in the form of objects and their properties, which have been conveyed through conventional learning methods and misconceptions of the learning materials. Adobe Animate was chosen as a learning medium because of its ability to present material visually, dynamically, and interactively. The study used a quantitative approach with a quasi-experimental design of the non-equivalent control group design, with the research subjects involving two different class groups of class IV of SDN 01 Panancangan, each as an experimental group (using Adobe Animate) and a control group (using conventional methods), with a total of 60 students. Data is collected through pretest, posttest, observation and documentation. The results of statistical analysis with t-test results indicated a significant difference between the learning outcomes of students in the experimental group and the control group (p < 0.05) which was 0.00, where the experimental group experienced a more significant increase in understanding. These findings support the assumption that the use of animation-based digital learning media can increase the effectiveness of the science learning process in elementary schools. Adobe Animate not only improves students' understanding of object concepts, interests, and engagement, but also helps them to represent concepts that are difficult to understand through verbal explanations. This research contributes to the development of innovative learning media, in line with the demands and characteristics of students in the 21st century era.